Pengaruh Downsizing, Free Assets, Dan Ukuran Perusahaan Terhadap Corporate Turnaround Studi Perusahaan Manufaktur Pada Bursa Efek Indonesia Tahun - Juhan Slamet Hirmanto; M Agus Salim; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACK             This study aims to determine how corporate turnaround is assessed in Indonesian stock exchange manufacturing companies in 2014-2018. In this study, the variables used to measure corporate turnaround are logistic regression analysis consisting of downsizing, free assets, and company size. Based on data from the Indonesia Stock Exchange, there are 15 manufacturing companies in the automotive sector. And of that total, there are only 13 manufacturing companies that match the criteria or qualify as the research sample. In determining this sample, researchers used a purpose sampling method, namely determining the sample with certain criteria. The results of this study prove that downsizing (DZ), free assets (FA), and company size simultaneously affect corporate turnaround. Downsizing (DZ) has a significant positive effect on corporate turnaround. Free asset (FA) has a significant positive effect on corporate turnaround.Keywords: Corporate Turnaround, Downsizing (DZ), Free Assets (FA),     Company Size